Determinants of Posttraumatic Stress Disorder (PTSD) among children and adolescents in the subacute stage of Kahramanmaras earthquake, Turkey - Neşe Yakşi; Mehtap Eroğlu (BMC, 2024)
Abstract Background Earthquakes are potentially traumatic natural disasters due to their destructive nature, and huge impacts, producing scenes of horror, undesirable and uncontrollable results. Children are affected mainly by earthquakes not only physically but also psychologically. We aimed to evaluate the rates of probable PTSD and related factors in children and adolescents after the February 6 Kahramanmaras earthquake. Methods In this cross-sectional study, 246 children and adolescents were included. The research was conducted in Hatay, one of the most affected provinces, between 06/07/2023-06/08/2023. Sociodemographic form, Children's Depression Inventory, Children's Posttraumatic Response Reaction Index, Screen for Child Anxiety Related Emotional Disorders, Child and Youth Resilience Measure and Social Support Appraisals Scale for Children were applied by face-to-face survey method. Results The median age of the participants was 12 (8-18). 133 (54%) of the participants were girls. Probable depression rate was 98%, and probable anxiety disorder rate was 63%. Probable mild, moderate, severe and very severe PTSD rates were 18%, 29%, 43% and 8%, respectively. The probable severe PTSD rate was higher in children who were injured in the earthquake (p = 0.032), who received outpatient treatment (p = 0.016), and who saw people trapped under the collapse (p = 0.012). Also, the children whose sleep routines have changed post-earthquake were found to have more probable severe PTSD (p < 0.001). Access time to the potable water supply (p = 0.045), toilet facilities (p = 0.045), shelter facilities (p = 0.004), heating facilities (p = 0.001), clothing supply (p < 0.001) and healthcare services (p = 0.009) were found to be associated with probable severe PTSD right after the earthquake. In the fifth month of the earthquake, inadequate meeting of clothing needs (p = 0.018), educational services (p = 0.028) and social activity opportunities (p < 0.001) were significantly associated with probable severe PTSD. In the multivariate analysis, the risk of probable severe PTSD was increased 2.9 times in those with post-earthquake sleep changes (p = 0.001) and 11.1 times in those with probable anxiety disorders (p < 0.001). Also, it has been shown that each unit increase in the APP-family score reduces probable severe PTSD risk by 2% (p = 0.002). Conclusion In the current study, the rates of probable PTSD, depression and anxiety disorders were considerably high. Probable anxiety disorder and sleep disturbance were significant predictors of probable severe PTSD. On the other hand, social support from family was found to be a significant protective factor for severe PTSD risk. We conclude that the lack of meeting needs that increase the risk of probable severe PTSD differs in the acute and subacute phases.